Recent trends in rehabilitation interventions for visual neglect and anosognosia for hemiplegia following right hemisphere stroke. (January 2011) - Kortte, Kathleen B; Hillis, Argye E
This article highlights the most recent findings regarding the rehabilitation interventions for the syndromes of visual neglect and anosognosia for hemiplegia that occur following right hemisphere stroke. We review papers published in the past 4 years pertaining to therapeutic approaches for these two syndromes in order to identify the trends in the development of effective interventions. Overall, it appears well recognized that visual neglect syndromes and awareness syndromes frequently co-occur and both include complex, multifaceted impairments leading to significant difficulties in daily life functioning following stroke. Thus, the interventions for these syndromes must be multifaceted in order to address the complex interplay of cognitive–behavioral–emotional components. There appears to be a trend for using combination therapeutic interventions that address these components.